Cell Phone and Your Health - Yakymenko, Igor; Sidorik, Evgeniy; Tsybulin, Alexander (My University, 2014)
This booklet was prepared in term of Social project “Science for Society” run by R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of NAS of Ukraine and supported by the National Academy of Sciences of Ukraine. The risks of excessive microwaves exposure due to intensive use of cell phones and preventive measures are demonstrated. The booklet is intended for a wide audience especially pupils, students, parents and teachers. Цей буклет підготовлено в рамках соціальної ініціативи «Наука – суспільству» Інституту експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького за підтримки Національної академії наук України. Висвітлено питання ризиків для здоров’я людини від надмірного користування мобільним телефоном, надано практичні рекомендації для зменшення таких ризиків. Для широкого кола читачів, особливо дітей та молоді, їхніх батьків та педагогів.
Мобільний телефон і твоє здоров’я
Keywords: mobile phone; health risk; children; youth; precautionary principle; мобільний телефон; ризики для здоров’я; діти; молодь; принцип упередження; кафедра екології та екоменеджменту